DAMPAK EKSPLOITASI ENERGI MIGAS BAGI EKONOMI DAERAH - Didik Susetyo (Department of Development Economics, Universitas Sriwijaya, 2007)
Exploitation of oil and gas has been done in the long time ago in South Sumatra. Last decade, many problems come up with decentralized responsibility to natural resources such as primary energy oil and gas between central and local government. Lack of community development activities was complained by native people because it could not generate local economic growth by multiplier effect. Empirically, many projects have already subsidied in some social activities, but those did not educate the native people surround the projects. It caused many enclaves facing dualism behaviour.In the decentralization era, the new paradigm emerge that many local governments want to share managing the production of primary energy sources, especially oil and gas. Meanwhile, the decline of production of oil and gas will cause future estimation of consumption and contribution to local budget. What's happen in the future exploitation of primary energy of oil and gas to local economic development? Empirically, it's still hope to support the main local budget by equalizing fund programs. The problem is how local economic growth by exploitating oil and gas resources without sacrificing the local sustainable development. Key Words: Impact, oil & gas energy, local economic